Tingkat Pengetahuan Kesiapsiagaan Resiko Bencana Tsunami disaat Pandemi Covid-19 - Rio Khoirudin Apriyadi; Rani Amelia (PendIPA Journal of Science Education, 2021)
[Knowledge Level about Tsunami Disaster Preparedness during the Covid-19 Pandemic] Indonesia is an archipelago located among 3 highly active tectonic plates namely Eurasia, Pacific and Indo-Australia. The plate activity resulted in Indonesia being rich in mining materials and minerals. But in addition to being profitable, the activity of the plate is also a potential source of disaster that can occur at any time. The disaster is likely to come without any prior cues, so precautions are needed to prevent or reduce the risk of a natural disaster. Building a culture of harmony coexisting with the risk of disaster, humans can live in accordance with nature. Knowledge of disaster preparedness is very necessary so that disasters can be in risk management so as not to cause harm to people. The research purpose was to find out the level of knowledge of students of SMKN 1 Sragi South Lampung  to tsunami risk preparedness during the Covid-19 pandemic in 2020. This research is quantitative descriptive which analyzed by univariate. The sample in this study amounted to 114 respondents. This study uses primary data. The data collection technique is the online google form questionnaire which was conducted in November 2020. This data was obtained directly from the respondents of Class X students of SMKN 1 Sragi South Lampung. The results of the research data showed that the class X students of SMKN 1 Sragi South Lampung had a fairly good knowledge of tsunami disaster risk management during the Covid-19 pandemic in 2020 with an average score of 66.